The Efficient Financial Management as a Practical Solution for Micro and Small Enterprises (MSEs) - Widati, Sindik; Fuadi, Agus; Wulandari, Dian Sulistyorini; Widiyaningsih, Widiyaningsih (Jurnal Pengabdian Pancasila (JPP), 2024)
This community service program aimed to enhance the financial literacy and management skills of local entrepreneurs. Recognizing the vital role of MSEs in driving economic growth, particularly in Cikarang Pusat, this program focused on providing tailored financial training and practical tools to improve budgeting, cash flow management, and record-keeping practices. Over two weeks, from September 8 to September 22, 2024, participants engaged in hands-on workshops, case studies, and one-on-one consultations. The program yielded significant results, with average improvements of 40% in key financial concepts, reflecting the effectiveness of the training. Participants rated the program highly, with satisfaction scores of 4.7 to 4.9, indicating the relevance and value of the content provided. The findings suggest that localized financial training can substantially benefit MSEs, enhancing their operational efficiency and contributing to the broader economic resilience of the community. The program also recommends expanding its duration and incorporating follow-up support to ensure continued growth and sustainability for MSEs in the region.